Self-Regulation of Slippery Deadlines: The Role of Procrastination in Work Performance - Steel, Piers; Taras, Daphne; Ponak, Allen; Kammeyer-Mueller, John (Frontiers in Psychology, 2022)
We investigated the causes and impact of procrastination on “slippery deadlines,” where the due date is ill-defined and can be autonomously extended, using the unique applied setting of grievance arbitration across two studies. In Study One, using 3 years of observed performance data derived from Canadian arbitration cases and a survey of leading arbitrators, we examined the effect of individual differences, self-regulatory skills, workloads and task characteristics on time delay. Observed delay here is a critical criterion, where justice is emphasized to be swift and sure. Hierarchical Linear Modeling established trait procrastination as a substantive predictor of observed delay, equivalent to the environmental contributors of arbitration procedure or external workload. Also, despite substantive negative consequence of delay for both arbitrators and their clients, arbitrators who scored one standard deviation above the mean in procrastination took approximately twice as long to write their decisions compared to arbitrators one standard deviation below the mean. In Study Two, we conducted a cross-sectional survey of a much larger group of American arbitrators, largely replicating the associated results from Study One. Consistent with Temporal Motivation Theory (TMT), trait procrastination was largely explained by expectancy, value, and sensitivity to time related traits and skills, which together accounted for majority of the variance in trait procrastination, leaving little left for other explanations. For example, perfectionism connection to procrastination appears to be distal, being fully mediated by each of TMT’s core variables. Finally, procrastination was largely synonymous with a deadline pacing style, indicating that observed delay can be used as a proxy for procrastination as long as little or no prior work was done (e.g., a u-shaped pacing style is not synonymous). In all, our results indicate that procrastination is rampant in the workplace and has seriously detrimental effects.